Evidence-based patient information programme in early multiple sclerosis: a randomised controlled trial. Issue 4 (8th October 2013) - Köpke, Sascha; Kern, Simone; Ziemssen, Tjalf; Berghoff, Martin; Kleiter, Ingo; Marziniak, Martin; Paul, Friedemann; Vettorazzi, Eik; Pöttgen, Jana; Fischer, Korbinian; Kasper, Jürgen; Heesen, Christoph
Abstract : Objective: To evaluate the efficacy of an evidence-based patient information programme aiming to increase informed choice in patients with early multiple sclerosis (MS). Background: Patients with early MS face a number of uncertainties concerning diagnosis, prognosis and effectiveness of immunotherapy. Prior studies suggest that evidence-based patient information combined with group education can promote informed choice in MS patients. Methods: A 12-month, six-centre, double-blind randomised controlled clinical trial with 192 patients with a diagnosis of confirmed relapsing-remitting MS or clinical isolated syndrome in Germany. A 4-h interactive evidence-based educational programme was compared with a 4-h MS-specific stress management programme. The primary endpoint was informed choice after 6 months comprising risk knowledge and congruency between attitude towards immunotherapy and actual immunotherapy uptake. Secondary endpoints included autonomy preference, decision autonomy, decisional conflict and satisfaction, anxiety and depression, and number of immunotherapies. Results: For the primary endpoint, a significant difference was shown with 50 of 85 (59%) participants in the intervention group achieving informed choice after 6 months compared with 18 of 89 (20%) in the control group (OR 0.2 (95% CI 0.1 to 0.4), p<0.001). Four weeks after the intervention, more participants in the intervention group showed good risk knowledge (difference between groups 39% (95% CI 26% to 53%), p<0.001). There were no significant differences between groups for attitude towards immunotherapy and for immunotherapy uptake. There were trends towards increased autonomy preference after the intervention and increased adherence to immunotherapies in the intervention group. Conclusions: The intervention significantly increased informed choice and relevant risk knowledge without negative side effects.